1995
DOI: 10.1037/0021-9010.80.5.565
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of interrater and internal consistency reliability of selection interviews.

Abstract: A meta-analysis of 111 interrater reliability coefficients and 49 coefficient alphas from selection interviews was conducted. Moderators of interrater reliability included study design, interviewer training, and 3 dimensions of interview structure (standardization of questions, of response evaluation, and of combining multiple ratings). Interactions showed that standardizing questions had a stronger moderating effect on reliability when coefficients were from separate (rather than panel) interviews, and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
279
2
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(300 citation statements)
references
References 58 publications
13
279
2
6
Order By: Relevance
“…Although we cannot rule out this possibility, it seems unlikely because our results are comparable to previous findings concerning interviewer reliability (Conway, Jako, & Goodman, 1995;Taylor & Small, 2002) and interview construct-related validity obtained in field ABILITY TO IDENTIFY CRITERIA samples (Conway & Peneno, 1999;Huffcutt, Weekley, et al, 2001;Schuler & Funke, 1989;Van Iddekinge, Raymark, Eidson, & Attenweiler, 2004).…”
Section: Limitationssupporting
confidence: 82%
“…Although we cannot rule out this possibility, it seems unlikely because our results are comparable to previous findings concerning interviewer reliability (Conway, Jako, & Goodman, 1995;Taylor & Small, 2002) and interview construct-related validity obtained in field ABILITY TO IDENTIFY CRITERIA samples (Conway & Peneno, 1999;Huffcutt, Weekley, et al, 2001;Schuler & Funke, 1989;Van Iddekinge, Raymark, Eidson, & Attenweiler, 2004).…”
Section: Limitationssupporting
confidence: 82%
“…This indicates that the constructs that the interview had intended to measure are of little importance in establishing interviewer impressions of a candidate (Conway, Jako, & Goodman, 1995). At the same time, the current study makes several substantial new contributions.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Pulakos, Schmitt, Whitney, and Smith (1996) showed that even for structured interview, which curbs the influence that individual interviewer's intuitions might exert on the procedure given the formal nature of the application and rating process (Campion, Pursell, & Brown, 1988), the differences are likely to be due to chance rather than any real effect, considering the variance in the validity of the individual interviewers' ratings. In addition, Conway, Jako, and Goodman (1995) suggested that because interrater reliability in unstructured interview is so low, its ratings could not account for more than 10% of the variance in the job performance criterion. In support of their findings, Cortina, Goldstein, Payne, Davison, and Gilliand's (2000) meta-analysis showed that unstructured interview rarely contributed to the prediction of job performance above and beyond the variance explained by cognitive ability and conscientiousness (change in R 2 ranging from .01…”
Section: Clinical Vs Actuarial Judgmentmentioning
confidence: 99%